Evolved Bmp6 enhancer alleles drive spatial shifts in gene expression during tooth development in sticklebacks. Issue 4 (23rd September 2021) - Stepaniak, Mark D.; Square, Tyler A.; Miller, Craig T.
Abstract: Mutations in enhancers have been shown to often underlie natural variation but the evolved differences in enhancer activity can be difficult to identify in vivo . Threespine sticklebacks ( Gasterosteus aculeatus ) are a robust system for studying enhancer evolution due to abundant natural genetic variation, a diversity of evolved phenotypes between ancestral marine and derived freshwater forms, and the tractability of transgenic techniques. Previous work identified a series of polymorphisms within an intronic enhancer of the Bone morphogenetic protein 6 ( Bmp6 ) gene that are associated with evolved tooth gain, a derived increase in freshwater tooth number that arises late in development. Here, we use a bicistronic reporter construct containing a genetic insulator and a pair of reciprocal two-color transgenic reporter lines to compare enhancer activity of marine and freshwater alleles of this enhancer. In older fish, the two alleles drive partially overlapping expression in both mesenchyme and epithelium of developing teeth, but the freshwater enhancer drives a reduced mesenchymal domain and a larger epithelial domain relative to the marine enhancer. In younger fish, these spatial shifts in enhancer activity are less pronounced. Comparing Bmp6 expression by in situ hybridization in developing teeth of marine and freshwater fish reveals similar evolved spatial shifts in gene expression. Together, these data support a model in which the polymorphisms within this enhancer underlie evolved tooth gain by shifting the spatial expression of Bmp6 during tooth development, and provide a general strategy to identify spatial differences in enhancer activity in vivo .